A passage to India - West, Clare; Forster, E. M. (Oxford University Press Oxford, 2009)
A mysterious incident at the Marabar Caves, involving Adela Quested, newly arrived from England, and the charming Dr. Aziz, an Indian doctor, leads to a drama that divodes the British and Indian communities in anger, distrust, and fear